2019
DOI: 10.1002/jum.15110
|View full text |Cite
|
Sign up to set email alerts
|

The Hyperechoic Appearance of the Deltoid Muscle on Shoulder Ultrasound Imaging as a Predictor of Diabetes and Prediabetes

Abstract: Objectives To evaluate whether the ultrasound appearance of the deltoid muscle in diabetic patients differs from that in obese nondiabetic patients. Methods Ultrasound images of the deltoid muscle from 137 type 2 diabetic patients (including 13 prediabetic patients) and 49 obese nondiabetic patients were blindly reviewed by 2 musculoskeletal radiologists, and by a third when arbitration was needed, to determine whether the appearance was “normal,” “suspected diabetes,” or “definite diabetes.” Age, sex, race, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…In a study observing the micro-structure and morphology of the Achilles tendons of patients with long-term DM using an electron microscope, it was reported that such tendons have reduced fiber diameter, increased collagen fiber bulk density, and abnormal fiber morphology (4). These findings themselves suggest possible mechanisms underlying the findings of other reports indicating that (a) the hyperechoic appearance of diabetic muscles in ultrasound imaging correctly predicted diabetes in 70 of 79 patients (5); (b) long-term diabetes is associated with a high prevalence of chronic Achilles tendinopathy, including hypoechogenicity, entheseal thickening, and enthesophytes (2,6); and (c) diabetic tendons demonstrate inferior elasticity (Young modulus), maximum load, and stiffness levels (7,8). Theoretically, these respective muscle morphological and tendon microstructural changes are the causes of diabetic muscle force compromise, in addition to being evidence of diabetic complications in tissues with low reparative capacity.…”
Section: Introductionmentioning
confidence: 91%
“…In a study observing the micro-structure and morphology of the Achilles tendons of patients with long-term DM using an electron microscope, it was reported that such tendons have reduced fiber diameter, increased collagen fiber bulk density, and abnormal fiber morphology (4). These findings themselves suggest possible mechanisms underlying the findings of other reports indicating that (a) the hyperechoic appearance of diabetic muscles in ultrasound imaging correctly predicted diabetes in 70 of 79 patients (5); (b) long-term diabetes is associated with a high prevalence of chronic Achilles tendinopathy, including hypoechogenicity, entheseal thickening, and enthesophytes (2,6); and (c) diabetic tendons demonstrate inferior elasticity (Young modulus), maximum load, and stiffness levels (7,8). Theoretically, these respective muscle morphological and tendon microstructural changes are the causes of diabetic muscle force compromise, in addition to being evidence of diabetic complications in tissues with low reparative capacity.…”
Section: Introductionmentioning
confidence: 91%
“…In our previous study, we demonstrated that a qualitatively assessed elevation in deltoid muscle echogenicity on US was both sensitive for and a strong predictor of a T2DM diagnosis [ 23 ]. In this first study of its kind, we confirmed that a sonographic quantitative assessment of the deltoid muscle GPEI, using muscle/bone ratios, is also sensitive and accurate for the detection of T2DM in both obese and non-obese cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…He and Kelley, in their study utilizing muscle biopsies of non-obese and obese patients with and without T2DM, demonstrated that intramuscular glycogen levels are decreased up to 65% in those with T2DM [ 55 ]. Multiple studies have also shown that decreased intramuscular glycogen levels in the postexercise state and in critically ill patients can be visualized on US as increased muscle echogenicity [ 23 , 56 59 ] and therefore cause an increase in the muscle/bone ratio. Further studies are necessary to verify these potential hypotheses and identify specific causation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations